Pengaruh Suhu Pemadatan Terhadap Workabilitas Perkerasan Beton Aspal Lapis Aus - Rostianti, Rostianti; Mashuri, Mashuri (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2015)
Asphalt concrete-wearing cource (AC-WC) pavement is the layer that directly in contact with vehicle tires. One that affects the performance of asphalt concrete is compaction. Optimal compaction can be met if the temperature in the compaction is carried on at a good temperature and in accordance with the specifications. The purpose of this study was to determine the compaction temperature workability best value on asphalt concrete wearing cource (AC-WC) pavement.  Tests were conducted on the condition of optimum bitumen content by 8 (eight) wide solidification temperature variation which were at the temperature of 70 ± 1˚C, 80 ± 1°C, 90 ± 1°C, 100 ± 1°C, 110 ± 1°C, 120 ± 1˚C, 130 ±1°C, and 140 ± 1°C. Testing was conducted by using the Marshall test instrument as substitutes for gyratory devices. Porosity measurements performed on Marshall blow mix of 2 × 5, 2 × 10, 2 × 20, 2 × 40, 2 × 60 and 2 × 75. Based on the equations of relationship between the logarithm of the number of gyratory rotation and porosity then the intercept value can be obtained which was then used to calculate workability index (WI) of the compaction temperature variations.  The result showed that all of them do not show good compaction workability value, because its value is less than 6. However, from the eight variations of the solidification temperature of solidification temperature of 130 ± 1 shows the best workability with WI = 4.031